ISLAMISASI DI KERAJAAN BIRA PADA ABAD XVII M - Zulkarnain Ambo (CV. Adiba Aisha Amira, 2023)
This thesis research discusses the process of Islamization in Bira in the XVII century in a historical review. The purpose of this research is to answer research questions, namely: 1. How was the condition of the Bira kingdom before the arrival of Islam, 2. How was the arrival and acceptance of Islam in the Bira Kingdom, 3. How was the development of Islam in the Bira Kingdom, the purpose of this research is three points, namely : first to explore, add and expand knowledge about the Bira Kingdom ahead of the arrival of Islam, Second, To add and broaden knowledge about the arrival of Islam in the Bira Kingdom, Third To know and understand the implementation of Islamization of the lives of the people of Bira Village. This type of research is qualitative research and data is obtained through field research and library research. The approach used in this study is historical analysis, in which historical research utilizes historical theory and methodology with research steps through heuristics, source criticism, interpretation and historiography. The results of this study indicate that, first, the condition of the Bira Kingdom at the beginning of the arrival of Islam where the people still adhered to animism and dynamism until Islam came and was accepted around 1604 to 1607 brought by Sheikh Abdul Rahman. The Islamization strategy is based on persuasive educative and top down approaches to Sufism and Shari'a so that Islam can be accepted as a whole in the kingdom of Bira. Second, the arrival of Islam in the Kingdom of Bira through trade channels and subsequently a missionary named Sheikh Abdurrahman and Sheikh Abdul Haris carried out intensive da'wah activities. Third, in 1604, Islam grew rapidly due to its peaceful spread and approach and the support of King Bira to V Bakka Daeng Bura'ne, who was converted to Islam by Sheikh Abdul Rahman who came to the Bira area. At the beginning of the development of Islam, the muballiq was able to occupy a strategic position in the royal environment as an advisor to the king as well as a channel of communication from the community to the kingdom, thus facilitating all policies related to Islam. The implication of this research is that it is hoped that the public will always know the stories and figures who contributed to the development of Islam in Bira, such as Sheikh Abdul Rahman and other figures. In addition, this area is expected to become an icon that is able to pass on strong Islamic values to the local generation